Papaverine hydrochloride containing nanostructured lyotropic liquid crystal formulation as a potential drug delivery system for the treatment of erectile dysfunction - Berkó S; Zsikó S; Deák G; Gácsi A; Kovács A; Budai-Szűcs M; Pajor L; Bajory Z; Csányi E (Dove Medical Press, 2018)
Szilvia Berkó,1 Stella Zsikó,1 Gábor Deák,2 Attila Gácsi,1 Anita Kovács,1 Mária Budai-Szűcs,1 László Pajor,2 Zoltán Bajory,2 Erzsébet Csányi1 1Institute of Pharmaceutical Technology and Regulatory Affairs, University of Szeged, Szeged, Hungary; 2Department of Urology, University of Szeged, Szeged, Hungary Purpose: Papaverine hydrochloride (PaHCl) is an old, well-known drug with spasmolytic activity but it has therapeutic effect in erectile dysfunction, too. As an intracavernous injection, it is not used in urologic clinics today because the side effects of the injection are pain, scarring or priapism. Our aim was to develop and test a topical semi-solid preparation containing PaHCl that would provide an alternative administration option by eliminating the undesirable side effects of the injection.Materials and methods: Lyotropic liquid crystal (LLC) systems were formulated as a semi-solid preparation with different concentrations of PaHCl. The characterization of the LLC structure was performed by polarization microscopy using a Leica image analyzer and rheological measurements. The drug diffusion and penetration tests were performed with in vitro synthetic membrane and an ex vivo human epidermis, using Franz diffusion cell to test the skin penetration of PaHCl. Human skin was investigated by Raman microscope to visualize the Active Pharmaceutical Ingredient (API) in different skin layers.Results: The results of diffusion and penetration showed reverse concentration dependency. The in vitro and ex vivo studies correlated with each other and the results of Raman microscopy. The LLC structure influenced the penetration results, the lower viscosity and lamellar structure increased penetration through the skin.Conclusion: Based on our results, a PaHCl containing topically used LLC formulation may be a suitable and effective alternative to the injectable formulation. Keywords: nanocarrier, dermal penetration, impotence, Raman microscopy